Health Inequalities in Diabetes Mellitus and Hypertension: A Parish Level Study in the Northern Region of Portugal - Leao, Teresa; Perelman, Julian; Felício, Manuela; Machado, Vasco; Lima, Graça (Acta Médica Portuguesa, 2016)
Introduction: Diabetes and hypertension are highly prevalent conditions in Portugal. Little is known about the geographical and social patterning of these diseases, which precludes the design of targeted health policies. This study aimed to measure the geographical and socioeconomic distribution of type 2 diabetes and hypertension prevalence in the population resident in the Northern region of Portugal, for the year 2013. Material and Methods: An ecological correlation study analyzed the 2,028 parishes of the region. Prevalence data were obtained from the Regional Health Administration information system. Socioeconomic data were also obtained from this administrative database and from the 2011 national census. The association between each socioeconomic indicator and age-standardized prevalence was measured using the difference in prevalence, population attributable risk, relative inequality index, and regression coefficient. Results: The prevalence of type 2 diabetes and hypertension was 6.16% and 19.35%, respectively, and varied across parishes. These prevalences were significantly associated with low educational level, low tertiary sector weight, unemployment, and low-income rate (with prevalence differences between the most and least advantaged deciles up to 1.3% and 5.3%, respectively). Socioeconomic factors accounted for up to 20% of prevalence. Discussion: This study design did not allow us to evaluate causality and it may underestimate these diseases prevalence or its association with socioeconomic factors, but its results are in line with the evidence from other countries. Conclusion: These results emphasize the socioeconomic and geographical patterning of major diseases associated with a high mortality, and the need of health policies targeting the most deprived parishes.